PENERAPAN KONSEP SOSIAL DAN BEHAVIOR SETTING PADA RUMAH ADAT BALI - Josephine Roosandriantini; Fernanda Yosefi Meilan (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Kristen Duta Wacana Yogyakarta, 2020)
Title: Application of the Social and Behavioral Setting Concept on Balinese Architecture The neighborhood is formed unique as a result of the activities, reactions as well as behavior of the individuals who are living in it. The formation of the neighborhood has a natural architectural meaning which is determined by the necessity of individuals related to the division of the nature of space. The division of the nature of space is very apparent in Balinese traditional houses, it consists of the private to the public spaces. The nature of space is also studied in architecture behavior, and in this study behavioral approach is used in seeing the relationship between the nature of space and the physical appearance of Balinese architecture. This approach is also observing the pattern of user behavior that occurs repeatedly to form a distinct environmental order. This research was conducted to identify the spatial division and the formation of behavioral setting in which the behavior patterns is defined. The purpose of this study is to understand how the concept of behavior setting is applied in Balinese traditional houses. The research method used is a descriptive qualitative, by collecting data based on literature research on Balinese architecture. The results of this study are to explain the human needs of each arrangement based on the nature of the space, and also determine the formation of behavioral setting concepts in the arrangement of Balinese traditional houses.